Bose Einstein Condensation of Excitons and Polaritons - Som, Sunipa (Bentham Science Publishers, 2024)
This reference book explains the fundamentals of Bose Einstein Condensation (BEC) in excitons and polaritons. It presents five chapters exploring fundamental concepts and recent developments on the subject. Starting with a historical overview of BEC, the book progresses into the origins and behaviors of excitons and polaritons. Chapters also cover the unique thermalization and relaxation kinetics of excitons, and the distinctive features of polaritons, such as lasing, superfluidity, and quantized vortices. The chapters dedicated to BEC in excitons and polaritons detail experimental techniques, theoretical modeling, recent advancements, and practical applications in a simplified way for beginners. This book serves as a resource for researchers, physicists, and students interested in the phenomena of BEC, providing insights into both the theoretical foundations and the practical implications of excitons and polaritons.